2018
DOI: 10.1155/2018/4386438
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Complement 3 Deposition in Children with Primary Nephrotic Syndrome

Abstract: Background This study aimed to investigate the clinical significance of complement 3 (C3) deposition in renal tubules of children with primary nephrotic syndrome (PNS). Methods The clinical and pathological characteristics of PNS were retrospectively reviewed in 99 PNS pediatric patients, who were divided into the C3 deposition and the non-C3 deposition groups. Results A total of 39 patients (39.39%) had renal tubule C3 deposition. In the C3 deposition group, the ratios of urine N-acetylglucosaminidase/creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Liu et al reported that compared with FSGS patients with no or mild tubulointerstitial injury, those with moderate or severe tubulointerstitial injury exhibited a lower level of serum C3 (31). Wang et al reported that nephrotic syndrome patients with C3 deposition in their renal tubules have more severe disease conditions, tubulointerstitial injury, and recurrence (32). We found that C3a bound to the tubular cells of FSGS patients and that C3a promoted the transcription of versican in tubular cells.…”
Section: Discussionsupporting
confidence: 51%
“…Liu et al reported that compared with FSGS patients with no or mild tubulointerstitial injury, those with moderate or severe tubulointerstitial injury exhibited a lower level of serum C3 (31). Wang et al reported that nephrotic syndrome patients with C3 deposition in their renal tubules have more severe disease conditions, tubulointerstitial injury, and recurrence (32). We found that C3a bound to the tubular cells of FSGS patients and that C3a promoted the transcription of versican in tubular cells.…”
Section: Discussionsupporting
confidence: 51%